Product-Service System (PSS) Strategy in Service Development at Akara Coffee & Space - Fadhilah, Septian Fuad Fadhilah; Wendy Febrianty Mardhiyah; Nanang Alamsyah (ARRUS Journal of Engineering and Technology, 2024)
This study explores the Product-Service System (PSS) strategy at Akara Space, a coffee shop that adopts a functional results approach to enhance efficiency and business growth. Using a descriptive qualitative method, data were collected through interviews and on-site observations to identify the most suitable PSS quadrants for the business. The findings suggest that Product Pooling, Outsourcing, and Functional Result quadrants are practical strategies. Product Pooling involves resource sharing with other businesses to reduce costs, optimize resource use, and build partnerships. Outsourcing focuses on delegating specific management functions to external providers, enabling Akara Space to maintain service quality while focusing on its core strengths. The Functional Result quadrant introduces a membership model, allowing customers to access services rather than owning products. This approach aligns with customer preferences for convenience and fosters loyalty, creating a steady revenue stream. Implementing these strategies can improve Akara Space’s efficiency, competitiveness, and adaptability in a dynamic market. By leveraging collaboration, resource optimization, and innovative service models, the business can achieve sustainable growth while delivering excellent customer experiences.